Application of Spectral Decomposition and RGB Blending for Delineation of “S” Channel At Asri Basin - Swasty Aninda Piranti; Shaska Zulivandama; Noor Cahyo Dwi Aryanto; Andi Agus Nur; Ildrem Syafri (BULLETIN OF THE MARINE GEOLOGY, 2020)
Gita member is part of Talang Akar Formation is known as hydrocarbon reservoir at Asri Basin, eastern part of South Sumatra. This formation consists of several depositional systems such as braided channel, meandering channel, fluvial-deltaic, and estuarine system. A channel system was an interesting system developed in the Asri Basin, however, to get the channel distribution in Asri Basin is quite challenging because the thickness of the channels caused its appearance is generally close or under seismic resolution, the existence of coal below our target also affects the impression of “S” sand on seismic data. In this study, spectral decomposition and RGB Blending have been successful to identify “S” sand. RGB Blending map is extracted from 15 Hz as low frequency, 45 Hz as middle frequency, and 75 Hz as high frequency. Our interpretation was applied at RGB Blending map and reveal the “S” sand is classified as a meandering channel depositional system with the main direction of the channel is Northeast – Southwest.Keywords: spectral decomposition, RGB Blending, Gita reservoir, Asri Basin: Anggota Gita merupakan bagian dari Formasi Talang Akar yang dikenal sebagai reservoar hidrokarbon di Cekungan Asri, Sumatra Selatan bagian timur. Formasi ini terdiri dari beberapa sistem pengendapan seperti sistem sungai teranyam, meander, fluvial-delta, dan estuari. Sistem pengendapan sungai purba di Cekungan Asri merupakan sistem yang menarik untuk dieksplorasi namun untuk mendapatkan persebaran sungai tersebut merupakan hal yang menantang dikarenakan tipisnya ketebalan sungai yang mengakibatkan kenampakannya pada data seismik berada disekitar atau bahkan dibawah resolusi seismik, keberadaan lapisan batubara dibawah target turut mempengaruhi kenampakan pasir “S” pada data seismik. Dekomposisi spektral serta RGB Blending yang diaplikasikan pada penelitian ini dapat mengidentifikasi pasir “S”. Peta RGB Blending diekstraksi dari beberapa frekuensi, yaitu frekuensi 15 Hz yang diambil sebagai frekuensi rendah, 45 Hz sebagai frekuensi tengah, dan 75 Hz sebagai frekuensi tinggi. Selanjutnya dilakukan interpretasi pada peta hasil RGB Blending dan menunjukkan pasir “S” diklasifikasikan sebagai sungai dengan sistem meander dengan arah utama sedimentasi adalah Timurlaut - Baratdaya.Kata kunci: dekomposisi spektral, RGB Blending, reservoar Gita, Cekungan Asri